Criteria for Assessing Exposure to Biomechanical Risk Factors: A Research-to-Practice Guide—Part 2: Upper Limbs - Francesca Graziosi; Roberta Bonfiglioli; Francesco Decataldo; Francesco Saverio Violante (Life)
Musculoskeletal disorders are the most prevalent occupational health problem and are often related to biomechanical risk factors. Over the last forty years, observational methods for exposure assessment have been proposed. To apply them effectively in the field, an in-depth knowledge of each methodology and a solid understanding of their actual predictive value and limitations are required. In this two-part guide, we discuss methods that have a solid scientific background, are based on expert consensus, and that do not require disproportionate technical, material, financial, and time resources. In Part 1, we focused on the Revised NIOSH Lifting Equation as a validated method for assessing manual material handling and discussed its application when dealing with task variability. In Part 2, we look at methods for the assessment of upper-limb biomechanical exposure in manual jobs. According to the above-mentioned criteria, we discuss methodologies proposed by the American Conference of Governmental Industrial Hygienists (ACGIH) and evaluate activities requiring high-speed continuous movement and the use of hand force, working with the arms above the shoulder level, to prevent localized fatigue in the upper extremities in cyclical work tasks. Finally, a preliminary proposal of a proportionate risk assessment of working duration in part-time jobs is presented.